Program Employee Gathering “Satukan Hati Selaraskan Tujuan” Dalam Menjalin Hubungan Baik Karyawan - Pramelani Pramelani; Ayu Lestari (Jurnal Komunikasi, 2019)
Employees are company assets. Therefore employees are needed for the growthof a company. Therefore, every employee must be able to work together, compact so that work productivity can increase. Establishing good relationships between employees, always maintained for each company. To further strengthen this relationship, the company needs to hold an employee gathering program intended for all workers in the company. In addition to being able to refresh themselves but also can build compactness in work the better. Thus, the researcher wants to know about the employee gathering program conducted by PT Kurnia Mitra Selaras in establishing good employee relations with the theme "Unite Hearts in harmony with Goals". The method used is descriptive qualitative. And the results of the research stated that the employee gathering program "Unite Hearts in harmony with the Goals" in establishing employee relations held on Saturday - Sunday, 3-4 February 2018 at Villa Teratai, Lembang, Bandung can run successfully where the program is in accordance with the event rundown participants felt happy to have a good effect on employee relations where the length of time they rarely communicate among fellow employees because of their respective work activities. Keywords: employee gathering, employee relations